2009
DOI: 10.1109/tdei.2009.5211868
|View full text |Cite
|
Sign up to set email alerts
|

Study on charge transport mechanism and space charge characteristics of polyimide films

Abstract: As a core component of ac drive electric locomotive, performance of inverter-fed motor directly influences the stability and reliability of locomotive running. However, insulation early failures occur frequently. Presently, polyimide film, as a special type of engineering plastic film, widely applied in turn to turn insulation and turn to ground insulation of inverter-fed motors is a kind of basic insulating material. This paper investigates charge transport mechanism and space charge characteristics of polyim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 24 publications
(17 reference statements)
0
39
0
Order By: Relevance
“…WITH the advantages of high temperature resistance (400 o C ), low temperature tolerance (-269 o C), radiation resistance and excellent dielectric properties, Polyimide (PI) that serves as a typical kind of engineering polymer material has been widely used in different fields, such as the aerial, nuclear, microelectronic industry,turn to turn insulation and turn to ground insulation of inverter-fed motors [1,2]. Many theoretical and experimental studies on its electrical properties have been performed.…”
Section: Introductionmentioning
confidence: 99%
“…WITH the advantages of high temperature resistance (400 o C ), low temperature tolerance (-269 o C), radiation resistance and excellent dielectric properties, Polyimide (PI) that serves as a typical kind of engineering polymer material has been widely used in different fields, such as the aerial, nuclear, microelectronic industry,turn to turn insulation and turn to ground insulation of inverter-fed motors [1,2]. Many theoretical and experimental studies on its electrical properties have been performed.…”
Section: Introductionmentioning
confidence: 99%
“…For the dielectric bulk, space charge results showed that large amounts of trapping states, including deep traps and shallow traps, were introduced in the PI/Al 2 O 3 nanocomposites [42,43]. When the specimens were experimented with corona-discharge existing, a number of electrons and holes were injected into the solid dielectric bulk.…”
Section: Corona-resistant Propertiesmentioning
confidence: 99%
“…At high temperature, charge injection from the electrode increases. The charges acquire more energy from the thermal excitation and travels deep into the bulk before being trapped [8]. That is to say, the mobility of charges may increase with rise in temperature, which facilitates transport of charge deep within the dielectric before it gets trapped.…”
Section: Trap Depth Estimationmentioning
confidence: 99%